ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN ONLINE (E-COMMERCE) TOKO ONLINE LAZADA.CO.ID DI KOTA SANGATTA - Andi Akzar Mukhlis; Muhammad Nawawi Dg Sibali; Angga Kusumah (Tinta Nusantara 2018 Vol.1, 2020)
The purpose of this study is to identify and examine the factors that will influence consumer decisions in online purchases (e-commerce) on internet users and online shoppers, the lazada.co.id online shop in the city of Sangatta. The method used is purposive sampling, where the researcher chooses a purposive sample subjectively. The results of this study are expected to be used as a means to develop knowledge about management in the field of e-commerce, especially e-commerce on Lazada.co.id. The research was conducted using primary data where research data will be collected by making questionnaires which are distributed directly to respondents